THE EFFECT OF ORGANIZATIONAL COMMITMENT, INTERNAL CONTROL, AND RELIGIOSITY ON FRAUD PREVENTION IN OPD OF PEKANBARU CITY WITH EMPLOYEE COMPETENCE AS A MODERATING VARIABLE - Syafira Mazaya; Firdaus AR; Dani Pratama (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Accounting fraud has attracted a lot of media attention and has become a prominent issue in both private and state-owned organizations. This encourages researchers to find the causes of fraud and how to prevent or minimize the occurrence of fraud. This study aims to test and analyze how organizational commitment, internal control and religiosity influence fraud prevention with employee competence as a moderator. The population of this study was the Pekanbaru city regional apparatus organization with a sample of 129 selected using saturated sampling techniques or using census sampling techniques. The analysis tool in this study is Partial least Square path analysis using SEM-PLS 4. The findings of this study indicate that organizational commitment and internal control have an effect on fraud prevention, on the other hand religiosity does not affect fraud prevention in Pekanbaru city OPDs. Furthermore, the findings of this study also show that competence does not moderate the influence of organizational commitment and internal control on fraud prevention in Pekanbaru city OPDs. On the other hand, competence moderates the influence of religiosity on fraud prevention in OPDs in Pekanbaru City.Keywords: Organizational Commitment, Internal Control, Religiosity, Fraud Prevention, and Competenc